2008
DOI: 10.1111/j.1600-0501.2008.01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of miniplates and miniscrews used for orthodontic anchorage: experience with 492 temporary anchorage devices

Abstract: During placement of miniscrews in the aveolar process, increased failure rates were noticed among those contacting adjacent roots. Failed miniscrews appeared to be surrounded with a greater volume of soft tissue. When more inflammation was present, the adjacent roots seemed to experience more resorption. Nevertheless, the created lesion was repaired with a narrow zone of mineralized tissue deposited on the root surface, which was likely cellular cementum, and was mainly filled with alveolar bone, with the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 18 publications
6
117
0
11
Order By: Relevance
“…On the other hand, there are some studies that did not reveal any differences in micro-implant stability in the maxilla or the mandible. Chen et al 20 stated that the quality of the bone itself rather than location is paramount for micro-screw fixation, which is in accordance with the studies published by Miyawaki et al 5 , who similarly concluded that cortical thickness overrides the issue of location itself. Nevertheless, the results of the meta-analyses clearly indicate that orthodontic micro-implants placed in the mandible have a higher risk of failure.…”
Section: Bone Anatomy and Histologysupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, there are some studies that did not reveal any differences in micro-implant stability in the maxilla or the mandible. Chen et al 20 stated that the quality of the bone itself rather than location is paramount for micro-screw fixation, which is in accordance with the studies published by Miyawaki et al 5 , who similarly concluded that cortical thickness overrides the issue of location itself. Nevertheless, the results of the meta-analyses clearly indicate that orthodontic micro-implants placed in the mandible have a higher risk of failure.…”
Section: Bone Anatomy and Histologysupporting
confidence: 80%
“…2,5,15,20,[30][31][32] Experimental studies show that a penetrating inflammatory process results in degeneration of the bone supporting the micro-implant that finally loses its stability. 32,33 Dalessandri et al proved that peri-micro-implantitis entails an almost 9-fold increase of the risk of micro-screw failure and seems to be one of the most important factors responsible for this complication.…”
Section: Susceptibility To Infl Ammationmentioning
confidence: 99%
“…[25][26][27][28][29] Miniplates have been shown to be well accepted as skeletal anchorage by both patients and providers and have turned out to be a safe and effective adjunct for complex orthodontic treatment. 24 However, the success rate of miniplates for skeletal anchorage in orthodontics [30][31][32][33] has not been investigated so thoroughly as that of miniscrews, and research has been limited to adolescent and adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of MIs to orthodontic practice, several studies investigated MI success rates and factors associated with MI failure (1,(5)(6)(7)(8)(9)(10). However, previous studies did not consistently define these outcomes, which complicate subsequent follow-up studies of MI success and failure rates.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies reported that oral hygiene is an important factor in MI success and survival (4,9,15,16). However, oral hygiene was not assessed in this study for two reasons.…”
Section: Discussionmentioning
confidence: 99%